Local Recurrence of Soft Tissue Sarcoma: A Radiomic Analysis - Tagliafico, Alberto Stefano (Radiol Oncol, 2019)
BACKGROUND: To perform a radiomics analysis in local recurrence (LR) surveillance of limb soft tissue sarcoma (STS) PATIENTS AND METHODS: This is a sub-study of a prospective multicenter study with Institutional Review Board approval supported by ESSR (European Society of Musculoskeletal Radiology). radiomics analysis was done on fast spin echo axial T1w, T2w fat saturated and post-contrast T1w (T1wGd) 1.5T MRI images of consecutively recruited patients between March 2016 and September 2018. RESULTS: N = 11 adult patients (6 men and 5 women; mean age 57.8 ± 17.8) underwent MRI to exclude STS LR: a total of 33 follow-up events were evaluated. A total of 198 data-sets per patients of both pathological and normal tissue were analyzed. Four radiomics features were significantly correlated to tumor size (p < 0.02) and four radiomics features were correlated with grading (p < 0.05). ROC analysis showed an AUC between 0.71 (95%CI: 0.55–0.87) for T1w and 0.96 (95%CI: 0.87–1.00) for post-contrast T1w. CONCLUSIONS: radiomics features allow to differentiate normal tissue from pathological tissue in MRI surveillance of local recurrence of STS. radiomics in STS evaluation is useful not only for detection purposes but also for lesion characterization.